Pemurnian Gliserol - Miftahul Khairati (Jurnal Jejaring Matematika dan Sains, 2022)
Glycerol is an alcoholic trihydrate which is hygroscopic. Glycerol can be obtained in several ways, namely hydrolysis of triglycerides to produce fatty acids and glycerol, saponification reactions of oils with alkaline bases to form alkali salts and glycerol, and trans-esterification reactions with alcohols to produce alkyl esters and glycerol. The glycerol obtained from the by-product of the reaction still contains a lot of impurities, so it needs to be purified so that the glycerol produced has a higher value. There are several ways to purify glycerol, including the acidification, which is adding strong acid to crude glycerol to bind the remaining base from the glycerol, the adsorption, which is the removal of impurities in the glycerol, and the distillation to evaporate the remaining methanol and water in the glycerol.